Trichoscopy in alopecia areata and trichotillomania in skin of colour: A comparative study - Siddharth Mani; Aradhana Raut; Shekhar Neema; Manish Khandare; Prateksha Golas; Sunmeet Sandhu; Rohit Kothari; Gopalsing R Rajput; Bhavni Oberoi (Wolters Kluwer Medknow Publications, 2023)
Alopecia areata (AA) and trichotillomania (TTM) are the two common causes of localised non scarring alopecia. While AA is an autoimmune disorder, TTM is an impulse control disorder which makes the treatment of the two entities completely different. Trichoscopy is a non-invasive tool used to diagnose hair disorders, which not only is extremely helpful in diagnosing AA and TTM but also differentiates them from other hair disorders as well. The aim of our study is to describe the various trichoscopic features of AA and TTM and to compare the frequency of each trichoscopic feature in order to establish diagnostic clues for differentiating AA and TTM. Trichoscopy was performed on clinically diagnosed cases of AA and TTM with DL4 dermoscope and the images were analysed by 2 dermatologists independently. The frequency of trichoscopic features in AA and TTM was compared using chi square test. Twenty-four patients of TTM and 50 patients of AA were included in the study with mean age of AA being 30 years and mean age of TTM being 23.4 years. Exclamation mark hair, tapered hair, coudability hair, pigtail hair, clustered vellous hair, clustered regrowing hair and white hair were significantly more in alopecia areata. Conversely broken hair of different length, trichoptilosis, flame hair, mace hair, coiled hair, hair powder, fractured hair, v sign and burnt matchstick sign were the common features in TTM. To conclude, even though there is an overlap of trichoscopic features in AA and TTM, it is possible to distinguish the two if an assemblage of specific features are present.